Progress in ozone sensors performance: a review - David, Michael (Penerbit UTM Press, 2015)
There has been a surge in ozone gas relevance in agriculture, environment and in the industry. This has resulted in increased research activities in areas involving ozone gas generation, application, safety and sensing. In this manuscript we present reviews of selected recent works (2011-2015) on ozone gas sensors based on absorption spectroscopy. Issues addressed include sensors applications versus requirements; sensors performance versus limitations and cost of sensors. Outstanding research issues are also outlined. While the review is mainly biased towards sensing of ozone using conventional absorption spectroscopy, other methods such as photo acoustic, photo reductive, photo stimulated, metal oxides, electrochemical, chemical, solid state and resistive ozone sensors were also considered in light of their performance criteria. Generally, it was observed that new applications of ozone gas lead to new sensing research challenges. Several sensing parameters were repeatedly investigated and improved upon over the years. Some of these parameters include: selectivity, sensitivity, speed of response, cost of sensor, lower detection limit and portability.